Effects of distant biofield energy healing on adults associated with psychological and mental health-related symptoms: a randomized, placebo-controlled, double-blind study - Mahendra Kumar Trivedi; Alice Branton; Dahryn Trivedi; Sambhu Mondal; Snehasis Jana (Health Psychology Research)
# Background